DAMPAK PENGEMBANGAN DESTINASI WISATA TUGU KHATULISTIWA TERHADAP EKONOMI MASYARAKAT PASCA COVID-19 - Purwoyo, Teguh Catur (Universitas Tanjungpura, 2024)
This research was conducted to determine the impact of developing tourist destinations on the economy of the surrounding community. This research was conducted at the Equator Monument in the city of Pontianak. This research is a type of descriptive research with a qualitative research form. Data collection techniques used by this researcher include: observation, interviews, and documentation. The informants in this study are the managers of the Equator Monument and the community. The results of the study that: the impact of developing tourist destinations on the community's economy is very good, moreover this equator monument is an icon of the city of Pontianak with this tourist destination can open business opportunities for people around the equator monument. In addition, it can reduce unemployment and increase the income of the community around tourism. The impacts before and after Covid-19, namely: the impact before the occurrence of Covid-19 on income, there was no decrease in traders' income. The impact after the occurrence of Covid-19 was that income was reduced a lot during Covid, before Covid it was running smoothly. It can cover the capital but during Covid, because the Equator Monument was closed, the income decreased a lot.